Dexmedetomidine Inhibits ASIC Activity via Activation of α2A Adrenergic Receptors in Rat Dorsal Root Ganglion Neurons - Wei, Shuang; Qiu, Chun-Yu; Jin, Ying; Liu, Ting-Ting; Hu, Wang-Ping (Frontiers in Pharmacology, 2021)
Dexmedetomidine (DEX), a selective α2 adrenergic receptor (α2-AR) agonist, has been shown to have peripheral analgesic effects in a variety of pain conditions. However, the precise molecular mechanisms have not yet been fully elucidated. Acid sensing ion channels (ASICs) are the major player in pain associated with tissue acidosis. Given that both α2-ARs and ASICs exist in dorsal root ganglia (DRG) neurons, we therefore investigated the effects of DEX on the functional activity of ASICs. Herein, whole-cell patch-clamp recordings demonstrated that DEX suppressed ASIC-mediated and acid-evoked currents and action potentials in dissociated rat DRG neurons. DEX shifted downwards concentration-response curve to protons, with a decrease of 35.83 ± 3.91% in the maximal current response to pH 4.5. DEX-induced inhibition of ASIC currents was blocked by the α2A-AR antagonist BRL44408 in DRG neurons. DEX also inhibited ASIC3 currents in CHO cells co-expressing ASIC3 and α2A-ARs, but not in ASIC3 transfected CHO cells without α2A-ARs expression. DEX-induced inhibition of ASIC currents was mimicked by the protein kinase A inhibitor H-89, and blocked by intracellular application of the Gi/o protein inhibitor pertussis toxin and the cAMP analog 8-Br-cAMP. In addition, peripherally administration of DEX dose-dependently relieved nociceptive responses to intraplantar injection of acetic acid in rats through local α2A-ARs. Our results indicated that DEX inhibited the functional activity of ASICs via α2A-ARs and intracellular Gi/o proteins and cAMP/protein kinase A signaling pathway in rat DRG neurons, which was a novel potential mechanism that probably mediated peripheral analgesia of DEX.